How to age disgracefully eaudiobook A novel. - Pooley, Clare (Books on Tape, 2024)
“An uproarious romp!” — People “Pooley weaves together the most cleverly flawed and lovable characters and then sets them free to prove that we are limitless at any age.” —Annabel Monaghan, bestselling author of Summer Romance A senior citizens’ center and a daycare collide with hilarious results in the new ensemble comedy from New York Times- bestselling author Clare Pooley When Lydia takes a job running the Senior Citizens’ Social Club three afternoons a week, she assumes she’ll be spending her time drinking tea and playing gentle games of cards. The members of the Social Club, however, are not at all what Lydia was expecting. From Art, a failed actor turned kleptomaniac to Daphne, who has been hiding from her dark past for decades to Ruby, a Banksy-style knitter who gets revenge in yarn, these seniors look deceptively benign—but when age makes you invisible, secrets are so much easier to hide. When the city council threatens to sell the doomed community center building, the members of the Social Club join forces with their tiny friends in the daycare next door—as well as the teenaged father of one of the toddlers and a geriatric dog—to save the building. Together, this group’s unorthodox methods may actually work, as long as the police don’t catch up with them first.